2019
DOI: 10.1093/intimm/dxz084
|View full text |Cite
|
Sign up to set email alerts
|

Heparin induces neutrophil elastase-dependent vital and lytic NET formation

Abstract: Heparin is used extensively as an anticoagulant in a broad range of diseases and procedures; however, its biological effects are not limited to coagulation and remain incompletely understood. Heparin usage can lead to the life-threatening complication known as heparin-induced thrombocytopenia (HIT), caused by the development of antibodies against heparin/PF4 complexes. Here, we demonstrate the ability of heparin to induce neutrophil extracellular traps (NETs). NETs occurred with cell lysis and death, but live … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…A large amount of heparin will produce antibodies against platelet factor 4 (PF4) and heparin complexes, leading to excessive activation of coagulation to activate platelets and promote thrombosis (Pouplard et al, 1999). In addition, heparin can directly induce the formation of NETs, but NETs cannot be induced by low molecular weight heparin, heparin analogs or heparin sulfate [low molecular weight heparin (LMWH), heparin mimetics or heparan sulfate] (Lelliott et al, 2020). However, there are also reports in the literature that heparin and heparin-derived drugs (including unfractionated heparin, LMWH and occasionally fondaparinux) can induce immune responses, leading to HIT (Perdomo et al, 2019).…”
Section: Heparinmentioning
confidence: 99%
“…A large amount of heparin will produce antibodies against platelet factor 4 (PF4) and heparin complexes, leading to excessive activation of coagulation to activate platelets and promote thrombosis (Pouplard et al, 1999). In addition, heparin can directly induce the formation of NETs, but NETs cannot be induced by low molecular weight heparin, heparin analogs or heparin sulfate [low molecular weight heparin (LMWH), heparin mimetics or heparan sulfate] (Lelliott et al, 2020). However, there are also reports in the literature that heparin and heparin-derived drugs (including unfractionated heparin, LMWH and occasionally fondaparinux) can induce immune responses, leading to HIT (Perdomo et al, 2019).…”
Section: Heparinmentioning
confidence: 99%
“…Heparin also replaces histones from the chromatin backbone of NETs, thereby destroying the stability of NETs ( 87 ). However, recent studies have shown that heparin stimulates NET formation in vitro , and the ability of enoxaparin to induce NET production is much lower than that of heparin, while pentosan sodium (fondaparinux) does not induce the formation of NETs ( 101 ). The hypothesis of the potential benefits of heparin therapy for patients with PE in real life requires further verification.…”
Section: The Role Of Nets In Venous Thrombosismentioning
confidence: 99%
“…These vesicles containing DNA are delivered through the cytoplasm and released extracellularly ( 31 ) ( Figure 1B ). This rapid NETosis is also reported when neutrophils are stimulated by Candida albicans ( 33 ), Leishmania parasites ( 34 ), heparin ( 35 ), and LPS-stimulated platelets ( 36 ). Unlike in suicidal NETosis, neutrophils releasing NETs rapidly do not undergo cell lysis and remain functional, thus this process is termed as vital NETosis ( 37 ).…”
Section: The Mesh-like Neutrophil Extracellular Trapmentioning
confidence: 67%